The “AIIMS hairpin loop” technique for ‘extreme’ volar rim fractures of distal radius - Garg, Bhavuk (J Clin Orthop Trauma, 2020)
Background: Treatment of distal radius fractures has seen a paradigm shift since the use of volar locking plates became popular. However, there is a subset of fractures, which includes extreme distal volar rim fractures, that is often not amenable to fixation by volar locking plates as there is insufficient bone mass to put screws. These fractures as such are quite rare but carry a huge morbidity due to frequent lack of anatomical reduction and fixation. A number of different techniques like hook plates, specially designed distal volar locking plates and loop wire techniques have been described for these fractures, but they have been found to be less helpful when the fracture fragments are very small. Methods: Herein, we describe our experience on 6 patients, using a novel surgical technique for fixation of distal radius volar rim fractures which works equally well even when the fragments are quite small (2–3 mm). The technique uses low cost and readily available implants (K wire and conventional volar locking plate) without the need of any special implants. Results: The total of 6 cases of distal radius volar rim fractures (AO/OTA Type B3 = 4, Type C1 = 2) were operated. The mean age was 50.83 years (range: 31–72). The mean follow-up duration was 43.3 months (range: 26–66). The mean size of the volar fragment was 3.66 mm (range: 2–5). The mean pronation and supination were 72.5° (60–80) and 74.2° (60–85). The main flexion and extension were 52.5° (40–75) and 58.3° (50–80) respectively. The mean grip strength was 19.8 kg (4–38) and it was mean 79.3% (40–130%) compared to uninjured side. The mean PRWE score was 12.3 (2–31). One patient developed symptoms of Complex Regional Pain syndrome 1 (CRPS 1) which resolved with conservative management and no other complications were noted. Conclusion: Our technique offers an indigenous, cost-effective way for fixation of extreme volar rim fracture fragments which can be easily adopted and used by surgeons in developing countries.